FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA IBU HAMIL DI WILAYAH KERJA PUSKESMAS MANDIANGIN KOTABUKITTINGGI - Ainal Mardiah (HUMAN CARE JOURNAL, 2020)
One of the highest causes of maternal death in Bukittinggi City is anemia. Mandiangin Health Center is the second highest Public Health Center with anemia, from 56 pregnant women as many as 29 pregnant women have anemia. The purpose of this study was to determine the relationship of economic status, education, employment, age, parity, and nutritional status with anemia of pregnant women in the working area of the Mandiangin Community Health Center in Bukittinggi City. This type of research is analytic descriptive with cross sectional approach. Samples amounted to 29 pregnant women, with sampling techniques with purposive sampling The results showed that there was a significant relationship between the incidence of anemia with economic status (p = 0.03), education (p = 0.02), employment (p = 0.04), age (p = 0.00), parity (p = 0.00) and nutritional status (p = 0.001). The conclusion of this study is that there is a relationship between economic status, education, employment, age, parity and nutritional status with anemia in pregnant women. It is recommended for pregnant women to be active in prenatal care so that anemia in pregnant women can be detected early